2017
DOI: 10.2527/jas.2016.1181
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate approach to determine the factors affecting response level of growth, carcass, and meat quality traits in finishing pigs fed ractopamine1

Abstract: The effect of ractopamine (RAC) supplementation on growth, carcass, and meat quality traits of finishing pigs was studied using a meta-analytical approach. The database was composed of 57 studies published from 2004 to 2016. The dependent variables extracted for the meta-analysis included final BW, ADG, ADFI, feed:gain ratio, HCW, dressing percentage, carcass length, lean yield, back fat thickness, loin muscle area, loin depth, postmortem pH, meat brightness, redness, and yellowness. The studies were grouped b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…Ciência Rural, v.54, n.5, 2024. the animals in the present study, increased weight gain is one of the effects frequently observed in studies that evaluate ractopamine supplementation (POMPEU et al, 2017).…”
Section: Ingredients % -----Control---------cromium------------rac---...supporting
confidence: 58%
See 2 more Smart Citations
“…Ciência Rural, v.54, n.5, 2024. the animals in the present study, increased weight gain is one of the effects frequently observed in studies that evaluate ractopamine supplementation (POMPEU et al, 2017).…”
Section: Ingredients % -----Control---------cromium------------rac---...supporting
confidence: 58%
“…The effects of ractopamine on carcass traits are well documented. Studies evaluating the use of ractopamine in the diet of finishing pigs generally indicate positive effects on the loin eye area, reduced backfat thickness, and increased amounts of lean meat (POMPEU et al, 2017). Ractopamine inhibits the binding of insulin to the β-adrenergic receptor, antagonizing its action, and reducing fat synthesis and deposition (ARMSTRONG et al, 2004).…”
Section: Ingredients % -----Control---------cromium------------rac---...mentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding ractopamine-supplemented diets for finishing pigs increases carcass lean mass and reduces the amount of carcass fat (POMPEU et al, 2017). The use of ractopamine in the diets for pigs is still allowed in Brazil; however, its use is banned in the European Union countries, China, and Russia (NIÑO et al, 2017).…”
Section: Introductionmentioning
confidence: 99%